Crossing Divides: Edinburgh International Festival Diary 2017. Issue 1 (February 2018) - Relich, Mario
Abstract : A review of the Edinburgh International Festivals on their (shared) 70 th anniversaries. The theme of 'crossing divides' is pursued.